STRATEGI PENGEMBANGAN PEMASARAN DAN PEMBUKUAN PADA UMKM RISOL MAYO “CAK GENDUT” - Indra Puji Astuti; Andy Febri Alexander; Devi Citra Mayasari (Jurnal Pengabdian Pendidikan Masyarakat (JPPM), 2024)
Competition for jobs is so tight that opening your own business is an alternative way of choosing a livelihood. Micro, Small and Medium Enterprises (MSMEs) are the most strategic social economic sector and concern the livelihoods of many people, making them the backbone of the national economy. However, the problems faced by the Risol Mayo "CAK GENDUT" business or small industries are mostly sources of capital, labor, raw materials for industrial processing and marketing. This community service related to assisting MSMEs with the Risol Mayo snack type is expected to provide solutions for MSMEs.The practical methods used in this mentoring program are observation and interview methods. There is a mentoring program for recording financial reports. The program carried out is a management approach related to working hours that is structured in a period of ≤ 4 weeks, utilizing social media, delivery services with a minimum purchase of IDR. 20,000 as well as innovation in gift coupons so that orders are not only made on a conversion basis and communication is very good between mentors and partners in achieving mentoring goals. It is hoped that MSME players can accept changes in information technology very quickly. MSME players are advised to innovate more aggressively in terms of marketing to attract consumers.